Moderate-vigorous physical activity and health-related quality of life among Hispanic/Latino adults in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) - Priscilla M. Vásquez; Ramon A. Durazo-Arvizu; David X. Marquez; Maria Argos; Melissa Lamar; Angela Odoms-Young; Donghong Wu; Hector M. González; Wassim Tarraf; Daniela Sotres-Alvarez; Denise Vidot; Rosenda Murillo; et al. (SpringerOpen, 2019)
Abstract Background Physical activity is a modifiable healthy behavior that has been shown to positively influence health-related quality of life. However, research examining the link between physical activity and health-related quality of life among Hispanic/Latino adults is limited and inconsistent. The purpose of this study is to assess whether accelerometer-measured moderate-vigorous physical activity (MVPA) is associated with self-reported (a) mental health-related quality of life, and (b) physical health-related quality of life among diverse Hispanic/Latino adults in the US. Methods Cross-sectional data from 12,379 adults ages 18-74 years in 2008-2011, who participated in HCHS/SOL and had complete data were analyzed using complex survey design methods. Accelerometer data were categorized into no MVPA, low, moderate, and high MVPA. Health-related quality of life was assessed with the Short-Form 12 and we used the mental and physical component subscales where higher scores indicate better health-related quality of life. Multivariate linear regression models were used to derive adjusted means with 95% confidence intervals and linear trends. Results We observed no significant linear trend between accelerometer-measured MVPA and mental health-related quality of life (ptrend = 0.73). There was a significant positive association between MVPA and physical health-related quality of life (ptrend < 0.001) where higher MVPA corresponded with higher scores in physical health-related quality of life. The adjusted means were 46.67 (44.85-48.48) for no MVPA, 49.33 (49.03-49.63) for low MVPA, 50.61 (50.09-51.13) for moderate MVPA, and 51.36 (50.86-51.86) for high MVPA. Conclusions Among diverse Hispanic/Latino adults in the US, accelerometer-measured MVPA was associated with physical health-related quality of life, but not mental health-related quality of life. Future interventions should evaluate if increases in MVPA lead to improvements in health-related quality of life.